Some Considerations of the Goal Setting and Planning Processes in Public Higher Education - Fleming, Thomas (Canadian Journal of Higher Education, 1978)
Too frequently the question of institutional purpose in higher education is unaddressed despite common agreement that it constitutes the critical core of organizational life. Resultantly, universities pursue complex programmes with little internal or external consensus on fundamental goals. This paper examines some important decision making areas in higher education and isolates a number of critical institutional variables which determine the nature of planning.